1984
DOI: 10.1103/physrevb.30.5871
|View full text |Cite
|
Sign up to set email alerts
|

Energy-band structure of chainlike polysilane(SiH2)nalloys

Abstract: The ener jy-band structure for ideal polysilane (SiH2)" is calculated using the Slater-Kostcr lineaI' combination of atomic orbitals (I.CAO) method. The interatomic matrix elements are estimated by us1Qg Harrison s Rppfox1matc 1cp1cscntat1oQ. From thc calculated band stfuctufc %'e dcducc that cha1nllke polysllanc 1S 8 scmlconductof hav1ng 8 verde d1rcct band gap Rnd thRt opt1CRl tI'Rnslt1ons RI'c allowed. This 1s cons1stcnt With thc experimental fcsults shovving 8 Wide opt1cal gap Rnd 41ghly efficient luminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…3. The measured optical bandgap is 3.1-3.2 eV for films deposited at a substrate temperature of -110'C, being in consistence with a theoretical value (3.1 eV) predicted for an ideal linear-chained polysilane [7].…”
Section: Optical Propertiessupporting
confidence: 54%
“…3. The measured optical bandgap is 3.1-3.2 eV for films deposited at a substrate temperature of -110'C, being in consistence with a theoretical value (3.1 eV) predicted for an ideal linear-chained polysilane [7].…”
Section: Optical Propertiessupporting
confidence: 54%
“…This implies that understanding of the energetics and the electronic and optical properties of the oligomers is fundamental to understand those properties in polysilanes. With the attention on oligomers as the ''chromophores'' in polysilane, semiempirical calculations with the Sandorfy C model Hamiltonian, 17,18 with MNDO 19 and ab initio 20 methods all concluded that the first absorption peak energy increases as the oligomer backbone becomes shorter. Semiempirical studies of oligosilane using MNDO for oligomers as long as 24 silicon atoms showed that the lowest lying optical absorption peak shifts to lower energy and then leveled off with oligomer length, much as given by the model Hamiltonian methods and observed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Semiempirical studies of oligosilane using MNDO for oligomers as long as 24 silicon atoms showed that the lowest lying optical absorption peak shifts to lower energy and then leveled off with oligomer length, much as given by the model Hamiltonian methods and observed experimentally. 1,[17][18][19] Ab initio studies using the Hartree-Fock and the more accurate CI methods were done for very short parent oligosilanes. 21,22 The first absorption peak energy was found to decrease with increasing silicon backbone angle and increase as the oligomer torsional conformation changes from trans to gauche.…”
Section: Introductionmentioning
confidence: 99%
“…12 Polysilane is a quasi one-dimensional semiconducting polymer whose basis is a conjugation, 13,14 and which has a direct type band structure with a band gap energy of more than 5.0 eV. 15 Since a low dimensional semiconductor such as polysilane has a large exciton binding energy of about 1.0-1.5 eV, the exciton level is usually observed as a sharp absorption band in the ultraviolet ͑UV͒ region between 300 and 400 nm.…”
mentioning
confidence: 99%